2015
DOI: 10.14712/23362936.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Mini Sling (Ophira) versus Pubovaginal Sling for Treatment of Stress Urinary Incontinence: A Medium-term Follow-up

Abstract: Sharifiaghdas F.; Nasiri M.; Mirzaei M.; Narouie B. Report / Vol. 116 (2015) No. 3, Mini Sling (Ophira) Key words: Mid-urethral mini sling -Autologous -Stress urinary incontinenceOphira Abstract: To compare two different procedures, mid-urethral mini sling (Ophira) and autologous rectus fascia sling, according to their medium-term subjective and objective outcome and satisfaction rates in the treatment of stress urinary incontinence in women. One hundred women with the main complaint of stress urinary inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The downfalls of pubovaginal slings reported were wound infections, obstructive symptoms and de novo urgency incontinence. 12 The reported incidence for de novo urge and urge incontinence post autologous sling surgeries were 15–20% and 7.2%, respectively; 13 which is similar to the incidence of this study in urgency and urge incontinence as 21% (23/109). This study had identified previous POP repair and over-tight technique to be related to patients seeking for treatment for de novo urgency incontinence after surgery.…”
Section: Discussionsupporting
confidence: 84%
“…The downfalls of pubovaginal slings reported were wound infections, obstructive symptoms and de novo urgency incontinence. 12 The reported incidence for de novo urge and urge incontinence post autologous sling surgeries were 15–20% and 7.2%, respectively; 13 which is similar to the incidence of this study in urgency and urge incontinence as 21% (23/109). This study had identified previous POP repair and over-tight technique to be related to patients seeking for treatment for de novo urgency incontinence after surgery.…”
Section: Discussionsupporting
confidence: 84%
“…18 Another cohort showed greater dyspareunia rates in minisling than in AFS at 12 months (11.4% vs 8.1%, P = 0.7). 17 However, these findings did not reach statistical significance in either study.…”
Section: Impact On Sexual Functionmentioning
confidence: 68%
“…Bleeding, as defined by estimated blood loss exceeding 250 mL and/or requiring blood transfusion, occurred infrequently and was similar between AFS and TVT groups, 11,14 as well as between AFS and minisling groups 17 . Two studies showed longer postoperative catheterization time in AFS than in TVT and minisling groups, 11,17 whereas another study showed equivalent rates between AFS and TVT 15 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations